English vocabulary word games & pictures for elementary level (Deepublish, 2016)
This book aims at helping English teachers to teach their students in a fun way as well as facilitating English learners to learn in an enjoyable way. It has particularly designed to teach and learn vocabulary for Elementary level, thus, the level of difficulty suits best learners ability. Pictures are provided throughout the book to help the learners understand the lessons well. For young learners to learn English, they need, in the words of Professor Stephen Krashen, Compelling Comprehensible Input. This book does that very thing ? by giving the young learners input via pictures and vocabulary reinforcement, the teacher has an excellent resource she may use in the classroom. Using this book with Professor Stephen Krashen?s latest methodology, TPRS (Teaching Proficiency through Reading and Storytelling), allows the teacher to concentrate on providing compelling input combined with the teacher?s creative storytelling.